V.2 - "Guha, Debashis" (New Delhi, 2007)
The series on Practical and Professional Ethics is an outcome of major Research project funded by the U.G.C. in which the task of resolving some value-laden practical problems troubling the professionals and the non-professionals in India was undertaken. Apart from clarifying the nature, tasks and interrelation of practical and professional ethics, volume one considers five categories of Ethical or value-laden practical problems such as environmental, biomedical, educational, economic and Business and socio-political ethics. It further deals with a range of value-laden environmental issues and contesting methodologies to resolve them. Justification of inter-subjective corroboration as the desirable Model in this regard and cases of practical urgency such as urbanization, harnessing Rivers and building dams for power generation and Nuclear options have been considered for value-resolution.
Keywords: Applied ethics